Factors Affecting Online Purchasing Power : Analysis of Sales Increase, Tight Competition and Price (Strategic Management Literature Review) - Fitriyani, Anisa (Siber International Journal of Education Technology (SIJET), 2024)
Factors affecting the Power of Online Purchasing: Analysis of Increased Sales, Tight Competition and Prices is a scientific article in the literature study within the scope of the field of science. The purpose of this article is to build a hypothesis of the influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. The research method with the research library comes from e-books and open access e-journals . The results of this article: 1) Increased Sales has an effect on Online Purchasing Power; 2) Intense Competition has an effect on Online Purchasing Power; and 3) Price has an effect on Online Purchasing Power.